Pengaruh Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Pegawai Kelurahan Di Kecamatan Penajam Kabupaten Penajam Paser Utara - Mahdalena Mahdalena; Mulyadi Hamid; St. Rukaiyah (Journal of Management and Social Sciences, 2024)
This research aims to determine and analyze the influence of leadership on the Performance of Regional Government Employees in North Penajam Paser Regency, determine and analyze the influence of Work Motivation on the Performance of Village Employees in Penajam sub-district, North Penajam Paser Regency and determine and analyze the Influence of leadership and Work Motivation on the Performance of Village Employees in Penajam sub-district, North Penajam Paser Regency. The research method used is quantitative descriptive research using Multiple Linear Regression data analysis using SPSS software. Primary data was obtained from respondents, namely Pegawai sub-district, Penajam sub-district, North Penajam Paser Regency. The population was 395 ASN and through sampling using the Slovin formula with a margin of error of 5%, a sample of 199 respondents was obtained. The results of the research show that partially there is a positive influence between Leadership and Work Motivation on the Performance of Village Employees in Penajam District, North Penajam Paser Regency. Together, leadership and work motivation also have a positive influence on the performance of village employees in Penajam District, North Penajam Paser Regency.